2021
DOI: 10.3389/fonc.2021.668247
|View full text |Cite
|
Sign up to set email alerts
|

PI3K Promotes Basal Cell Carcinoma Growth Through Kinase-Induced p21 Degradation

Abstract: Basal cell carcinoma (BCC) is a locally invasive epithelial cancer that is primarily driven by the Hedgehog (HH) pathway. Advanced BCCs are a critical subset of BCCs that frequently acquire resistance to Smoothened (SMO) inhibitors and identifying pathways that bypass SMO could provide alternative treatments for patients with advanced or metastatic BCC. Here, we use a combination of RNA-sequencing analysis of advanced human BCC tumor-normal pairs and immunostaining of human and mouse BCC samples to identify a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…However, SMO mutations driving drug resistance are common, and up to 21% of patients treated with vismodegib were found to undergo tumor regrowth during treatment ( 3 ). Additional pathways that contribute to BCC drug resistance include phosphatidylinositol 3-kinase (PI3K)/MTOR (Mammalian target of rapamycin) ( 4 , 5 ), WNT ( 6 ), aPKC ι/λ ( 7 ), NOTCH1 ( 8 ), RAS/MAPK ( 9 , 10 ), and activation of MRTF ( 11 , 12 ), to name a few. New therapeutic options are needed to treat advanced BCC.…”
Section: Introductionmentioning
confidence: 99%
“…However, SMO mutations driving drug resistance are common, and up to 21% of patients treated with vismodegib were found to undergo tumor regrowth during treatment ( 3 ). Additional pathways that contribute to BCC drug resistance include phosphatidylinositol 3-kinase (PI3K)/MTOR (Mammalian target of rapamycin) ( 4 , 5 ), WNT ( 6 ), aPKC ι/λ ( 7 ), NOTCH1 ( 8 ), RAS/MAPK ( 9 , 10 ), and activation of MRTF ( 11 , 12 ), to name a few. New therapeutic options are needed to treat advanced BCC.…”
Section: Introductionmentioning
confidence: 99%
“…Chow et al . 9 have demonstrated that the phosphatidylinositol 3-kinase (PI3K) pathway is essential for promoting tumor cell survival and proliferation. Therefore, the disorder of lipid metabolism and the development of tumors are closely intertwined and may impact the biological characteristics of cancer cells, such as proliferation, metastasis, and drug resistance, ultimately affecting the prognosis of the tumor.…”
Section: Lipid Metabolism and Pcamentioning
confidence: 99%
“…Treatment of murine keratinocytes and BCC cells with tazarotene significantly reduced Gli mRNA expression [ 157 , 161 ]. The PI3 kinase-AKT-mTOR pathway is also important for BCC pathogenesis, in part by dysregulating the cell cycle and promoting proliferation [ 162 ]. So et al demonstrated that tazarotene represses overactivation PI3 kinase-AKT-mTOR signaling in murine BCCs [ 163 ].…”
Section: The Molecular Mechanisms Of Retinoid Activity In Experimenta...mentioning
confidence: 99%